Production of Pseudomonas aeruginosa LBI rhamnolipids following growth on Brazilian native oils - Costa, SGVAO; Nitschke, M.; Haddad, R.; Eberlin, M. N.; Contiero, Jonas [UNESP] (Elsevier B.V., 2006)
Oils from Buriti (Mauritia flexuosa), Cupuacu (Theobroma grandiflora), Passion Fruit (Passiflora alata), Andiroba (Carapa gitianensis), Brazilian Nut (Bertholletia excelsa) and Babassu (Orbignya spp.) were evaluated as carbon sources for rhamnolipid production by Pseudomonas aeruginosa LBI. The highest rhamnolipid concentrations were obtained from Brazilian Nut (9.9 l(-1)) and Passion Fruit (9.2 g l(-1)) oils. Surface tension varied from 29.8 to 31.5 mN m(-1), critical micelle concentration from 55 to 163 mg l(-1) and the emulsifying activity was higher against toluene (93-100%) than against kerosene (70-92%). Preliminary characterization of the surfactant mixtures by mass spectrometry revealed the presence of two major components showing m/z of 649 and 503, which corresponded to the dirhamnolipid (Rha(2)C(10)C(10)) and the monorhamnolipid (RhaC(10)C(10)), respectively. The monorhamnolipid detected as the ion of m/z 503 is predominant in all samples analyzed. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: biosurfactants; glycolipids; Pseudomonas aeruginosa; rhamnolipids; surface-active compounds